2013
DOI: 10.3945/ajcn.112.049494
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of oral omega-3 PUFA in solar-simulated radiation-induced suppression of human cutaneous immune responses

Abstract: Oral n-3 PUFAs appear to abrogate photoimmunosuppression in human skin, providing additional support for their chemopreventive role; verification of study findings is required. This trial was registered at clinicaltrials.gov as NCT01032343.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 58 publications
(73 reference statements)
0
48
0
Order By: Relevance
“…To date there has been no comprehensive review of existing epidemiological data regarding the relationship between dietary n‐3 PUFAs and the incidence of skin cancer, although a number of potentially relevant biological mechanisms have been proposed . In vitro , n‐3 PUFAs not only protect against UV‐induced damage but promote appropriate immunological responses and hairless mice given diets rich in n‐3 PUFAs show significant reductions in cutaneous malignancy through promotion of tumor latency and inhibition of tumor multiplicity .…”
mentioning
confidence: 99%
“…To date there has been no comprehensive review of existing epidemiological data regarding the relationship between dietary n‐3 PUFAs and the incidence of skin cancer, although a number of potentially relevant biological mechanisms have been proposed . In vitro , n‐3 PUFAs not only protect against UV‐induced damage but promote appropriate immunological responses and hairless mice given diets rich in n‐3 PUFAs show significant reductions in cutaneous malignancy through promotion of tumor latency and inhibition of tumor multiplicity .…”
mentioning
confidence: 99%
“…[14][15][16][17] Recent studies evidence the extensive cutaneous profile of lipid mediators in human skin, encompassing the endocannabinoids, NAE, sphingolipids and eicosanoid families. [17][18][19][20][21] Some of these lipid species are known to be modulated by UVR and to play a role in photobiological effects in humans 22,23 whilst the potential involvement of the endocannabinoids and their congeners in UVRinduced effects, awaits further exploration. The main endocannabinoids anandamide (AEA) and 2-arachidonoyl glycerol (2-AG), and a range of N-acyl ethanolamine (NAE) species, derive from membrane lipids (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The Omega‐3 polyunsaturated fatty acid (n‐3 PUFA) eicosapentaenoic acid (EPA) reduces UVR suppression of CMI in vivo; in mice, both topical and systemic EPA‐rich lipids reduced UVR suppression of chemically induced CHS responses by up to 90% . Further, we recently observed in a randomised controlled trial (RCT) in humans that oral EPA supplementation showed potential to reduce UVR suppression of nickel CHS . While the mean group difference for the three solar‐simulated radiation (SSR) doses we employed showed no statistically significant protection by EPA, ~50% reduction of photoimmunosuppression was noted with UVR dosing equivalent to brief exposure to summer sunlight (post hoc analysis P <.05) .…”
Section: Introductionmentioning
confidence: 88%